2020
DOI: 10.3389/fnins.2020.00636
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Sleep and Circadian Rhythms in Schizophrenia and Their Interaction With Dopamine Signaling

Abstract: Sleep and Circadian Rhythms in Schizophrenia the pathophysiology of schizophrenia. Improvements in sleep are associated with improvements in symptoms, along with quality of life measures such as cognitive ability and employability. Therefore the circadian system holds valuable potential as a new therapeutic target for this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 145 publications
(170 reference statements)
2
36
1
3
Order By: Relevance
“…Consistently, the severity of symptom expression in ASD and schizophrenia scaled to the degree of impairment in the generation of gamma band oscillation (Edgar et al, 2015; Grent-’t-Jong et al, 2018). Furthermore, ASD and schizophrenia are commonly associated with disturbances in the sleep-wake cycle (Ashton and Jagannath, 2020; Ballester et al, 2020), of which transitions in sleep states may require modulation of electrical synapses in the reticular thalamus by chemical synaptic transmission (Coulon and Landisman, 2017). The foregoing indicates that agents which upregulate electrical synaptic transmission (Urbano et al, 2007; Beck et al, 2008) may benefit individuals with syndromes due to Shank3 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the severity of symptom expression in ASD and schizophrenia scaled to the degree of impairment in the generation of gamma band oscillation (Edgar et al, 2015; Grent-’t-Jong et al, 2018). Furthermore, ASD and schizophrenia are commonly associated with disturbances in the sleep-wake cycle (Ashton and Jagannath, 2020; Ballester et al, 2020), of which transitions in sleep states may require modulation of electrical synapses in the reticular thalamus by chemical synaptic transmission (Coulon and Landisman, 2017). The foregoing indicates that agents which upregulate electrical synaptic transmission (Urbano et al, 2007; Beck et al, 2008) may benefit individuals with syndromes due to Shank3 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from schizophrenia are very relevant to delusional disorders because of the considerable overlap between the two disorders. In schizophrenia, sleep quality has been correlated with the degree of paranoid ideation [ 36 ], with hostility and violence [ 37 ], with poor quality of life [ 38 , 39 ], with memory functions [ 40 ], with physical activity [ 41 ], and with dopamine signaling [ 42 ]. These correlations may well also apply to DD.…”
Section: Sleep and Psychosismentioning
confidence: 99%
“…Furthermore, the longer the sleep deprivation, the more detrimental its effect. The speculation is that disrupted dopamine pathways serve as the link between sleep and psychotic manifestations [ 42 ].…”
Section: Association Of Sleep Disturbances With Common Symptoms Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, DA in turn affects the circadian system by controlling the expression of a clock protein PER2 via striatal D2R (Hood et al, 2010). In schizophrenia, there is a bidirectional relationship between the DA system and circadian rhythm, and perturbation to one system can cause disruption in the other system (Ashton and Jagannath, 2020). A recent study in mice found that a mutated Clock gene increased firing rate in VTA DA neurons during daytime when mice are inactive, which led to manic-like behavior (Sidor et al, 2015).…”
Section: Subthreshold Membrane Activity and Circadian Rhythmmentioning
confidence: 99%